KOMPONEN INTI IMPLEMENTASI KURIKULUM 2013 PADA MATA PELAJARAN ISMUBA DI SMP MUHAMMMADIYAH 4 BANDAR LAMPUNG - Nisa Rahmania; Arizal Eka Putra; mashdaria huwaina (Universitas Muhammadiyah Lampung, 2023)
ABSTRACTThe 2013 curriculum that was implemented in the 2013/2014 school year. The emphasis point in the 2013 Curriculum is the improvement and balance of soft skills and hard skills. ISMUBA (Al-Islam, Kemuhammadiyahan, and Arabic) is a special feature and advantage of the Muhammadiyah School with an integrative-holistic Medern Islamic education system, in the form of a public school that integrates Islamic religious knowledge, and a madrasah that integrates general sciences. Based on this, researcher conducted research at SMP Muhammadiyah 4 Bandar Lampung with the title â€œImplementation of the 2013 Curriculum in ISMUBA Subjects at SMP Muhammadiyah 4 Bandar Lampungâ€.This research focuses on Islamic/Islamic Religious Education Subjects because these three subjects are allied subjects and there is no significant difference, so i tis deemed sufficient to sample Al-Islam subjects.The purpose of this research is to find out how the 2013 Curriculum is implemented and how the supporting and inhibiting factors are in its implementation. This research uses field research with a qualitative descriptive approach.The results of this research indicate that, (1) Implementation of the 2013 Curriculum has been implemented since 2019. In the 2022/2023 school year, the 2013 Curriculum has been impelemented in all classes. (2) Supporting and inhibiting factors, including; Implementation of socialization and training, teacher competence, availability of school facilities and infrastructure, student motivation, as well as evaluation or assessment of the 2013 Curriculum.Â Key Words : Implementation, 2013 Curriculum, Islamic Religiou Subject.